AKUNTANSI KELEMBAGAAN EKONOMI SYARIAH DALAM PERSFEKTIF IWAN TRIYUWONO - Rahmaniar Rahmaniar; Ahmad Dahoir (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2017)
Islam as a religion has been placed as an option and at the same teachings that provide guidance in human life adherents. Islamic economic development in Indonesia is progressing very rapidly, characterized by the emergence of sharia based financial institution. Financial institutions in practice cannot be separated from the financial statements or called in the language of business is accounting. This study focused on mentation of Iwan Triyuwono about the concept of sharia accounting, as stated in this theory that sharia enterprise theory and synergy binary opposition. The formulation of the problem in this study are (1) how the concept mentation of Iwan Triyuwono about sharia accounting? (2) how the relevance mentation of Iwan Triyuwono about accounting institutional of Islamic economics? Therefore the purpose of this study were (3) to describe the concept mentation of Iwan Triyuwono about sharia accountting (4) to describe the relevance mentation of about acoounting institutional of Islamic economics. This type of research is the library research using hictorical research aproach, namely research conducted by collecting data or scientific papers aimed at the object of research or data collection is literature, or the study undertaken to solve a problem on basically rests on a critical and in depth study of the materials relevant book. The subjects used in this study is Iwan Triyuwono. The results of this study indicate that the mentation of Iwan Triyuwono with shariah enterprise theory and the theory of binary opposition synergies already very relevan to formulate theories that previously exsited in modern accounting theory. But in practice has not been able to be applied fully in the Islamic economics institutions. Because of the needs of the industry if sharia accounting concept he put forward can be realized with either the creation of a network organization with the realities if divine power.